Performance Evaluation and QoS Optimization of LTE-WLAN Aggregation in Small Cell Networks - Wijanto, Eddy; Sutanto, Kevin (Faculty of Engineering, Universitas Tanjungpura, 2025)
The rapid surge in mobile data traffic continues to strain cellular networks, especially in dense urban areas where spectrum resources are limited. Long Term Evolution